Carbon Stock of Agroforestry Systems at Adjacent Buffer Zone of Lore Lindu National Park, Central Sulawesi - . Wardah; Bau Toknok; . Zulkhaidah (UNIVERSITY OF LAMPUNG, 2011)
The potential of agrofrestry to sequestrate carbon varies depending on the natural quality of sites and management practices. Agroforestry is a climate change mitigation activities. The aim of study was to estimate the carbon stock of agroforestry system at adjacent buffer zone of Lore Lindu National Park (LLNP). Research was carried out in two types of agroforestry stands (simple and complex) adjacent LLNP buffer zone in Palolo Sub District, Sigi District, Central Sulawesi. Estimation of biomass of tree, herbs, litter, necromass and root was based on an allometric equation. The carbon storage in soil was estimated based on the carbon organic content and bulk density of soil in30 cm of depth. The results of study showed that the total carbon stored in the simple agroforestry (125.97 MgC ha-1) was significantly lower than in the complex agroforestry (209.39 MgC ha-1). In addition, the aboveground carbon stock biomass (tree, herbaceous, necromass and litter) and belowground carbon stock (root and soil organic) in a simple agroforestry were 42.42 MgC ha-1 and 83.55 MgC ha-1, respectively. Whereas, the aboveground carbon stock biomass and belowground carbon stock in the complex agroforestry were 98.46 MgC ha-1 and 110.93 MgC ha-1, respectively. Based on the carbon stock estimation in six agroforestry plots in the buffer zones of Lore Lindu National Park, the complex agroforestry was likely to be more stable and more longer in storing carbon comparedto the simple agroforestry.Keywords: Agroforestry, biomass, carbon, climate change, Lore Lindu National Park